Measuring Ownership, Control, and Use of Assets - Kilic, Talip (Taylor and Francis, 2021)
Assets generate and help diversify income, alleviate liquidity constraints, and are key inputs into empowerment. Despite the importance of individual-level data on asset ownership, and the fact that most assets are owned by individuals, either solely or jointly, researchers typically collect micro data on asset ownership at the household level. Through a review of the existing approaches to data collection and the relevant literature on survey methodology, this study presents an overview of the current best practices for collecting individual-level data on the ownership and control of assets in household and farm surveys in low- and middle-income countries. The paper provides recommendations in three areas: (1) respondent selection, (2) definition and measurement of access to and ownership and control of assets, and (3) measurement of quantity, value, and quality of assets. It identifies open methodological questions that can be answered through further research.